1988
DOI: 10.1016/0014-5793(88)80903-7
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of pure βγ‐subunits of G‐proteins with purified β1‐adrenoceptor

Abstract: The role of the βγ‐subunits in the interaction of G‐proteins was examined with β1‐adrenoceptors purified from turkey erythrocytes and pure βγ‐subunits prepared from turkey erythrocytes and bovine brain. On a non‐denaturing polyacrylamide gel, the mobility of βγ‐subunits was increased when incubated with β1‐adrenoceptor and the β1‐adrenergic agonist l‐(−)‐isoproterenol, whereas on incubation with the antagonist l‐alprenolol the mobility was unchanged. Furthermore, the β1‐adrenoceptor was retarded on a Sephadex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Previously, we have shown that isolated bovine brain pisubunits can associate with the p,-adrenoceptor purified from turkey erythrocyte membranes (Im et al, 1988;Kurstjens et al, 1991). The j-adrenoceptor seems not to be the only hormone receptor which can couple to By-subunits.…”
mentioning
confidence: 91%
“…Previously, we have shown that isolated bovine brain pisubunits can associate with the p,-adrenoceptor purified from turkey erythrocyte membranes (Im et al, 1988;Kurstjens et al, 1991). The j-adrenoceptor seems not to be the only hormone receptor which can couple to By-subunits.…”
mentioning
confidence: 91%
“…5). For example, direct interactions of fry complexes with receptors have been shown by biochemical and biophysical means (6)(7)(8). The (By subunit complexes have also been shown to be capable of interacting with effectors.…”
mentioning
confidence: 99%
“…Values represent means ± SE of three experiments. receptor (9). Also transducin fry subunit (T13)-induced enhancement of rhodopsin-transducin linkage reaches saturation at the To-, concentration lower than that of the transducin a subunit (Ta) (7), suggesting that Tpy acts catalytically on Ta.…”
Section: Resultsmentioning
confidence: 99%
“…However, direct interactions of receptors with Ga remain to be demonstrated by using purified proteins. Several reports indicate that Go, directly interacts with the /3-adrenergic receptor or rhodopsin (7)(8)(9); the possibility that Ga indirectly interacts with receptors through Gab remains. Furthermore, it is unclear whether Gay stoichiometrically or catalytically acts on the receptor-Ga linkage, although it has been shown that Gab enhances this linkage (10,11).…”
mentioning
confidence: 99%